Diuqin lechiguanae gen. et sp. nov., a new unenlagiine (Theropoda: Paraves) from the Bajo de la Carpa Formation (Neuquén Group, Upper Cretaceous) of Neuquén Province, Patagonia, Argentina - Porfiri, Juan Domingo (2024)
Here we describe Diuqin lechiguanae gen. et sp. nov., a new unenlagiine taxon from the Upper Cretaceous (Santonian) Bajo de la Carpa Formation of the Neuquén Basin of Neuquén Province in northern Patagonia, Argentina that fills a substantial stratigraphic gap in the fossil record of these theropods. Although known only from a very incomplete postcranial skeleton, the preserved bones of Diuqin differ from corresponding elements in other unenlagiines, justifying the erection of the new taxon. Moreover, in several morphological aspects, the humerus of Diuqin appears intermediate between those of geologically older unenlagiines from the Neuquén Basin (e.g., Unenlagia spp. from the Turonian–Coniacian Portezuelo Formation) and that of the stratigraphically younger, larger-bodied Austroraptor cabazai from the Campanian–Maastrichtian Allen Formation. Consequently, the morphology of the new taxon appears to indicate a transitional stage in unenlagiine evolution. Phylogenetic analysis recovers Diuqin as a paravian with multiple plausible systematic positions, but the strongest affinity is with Unenlagiinae. The humerus of the new form exhibits subcircular punctures near its distal end that are interpreted as feeding traces most likely left by a conical-toothed crocodyliform, mammal, or theropod, the latter potentially corresponding to a megaraptorid or another unenlagiine individual. Thus, in addition to filling important morphological and temporal gaps in unenlagiine evolutionary history, the new taxon also offers information relating to the paleoecology of these theropods.